PENGARUH POLA ASUH IBU TERHADAP PRESTASI ANAK DI SDN 03 BUANA BAKTI KECAMATAN KERINCI KANAN KABUPATEN SIAK - ", Satriyana; Tantoro, Swis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The flurry of husband and wife because of the encouragement to be able to support his family and to meet the economic needs of the family every day is a factor both parents to work as a result of their attention and parenting of children become less. The aim of this study is to determine the form of parenting mother to child, to determine the effect of the mother's parenting achievement levels of children Data analysis was conducted by way of explaining the data into the form of quantitative descriptive analysis complete with percentages and cross table to see the strong influence of variables declared in the correlation coefficient does purposes of data analysis is to test the hypothesis in this study. The analysis used is all of the data obtained in the field both primary and secondary data and will be grouped according to type and then quantitatively analyzed descriptively. The population in this study are all parents (mother) Grade 5 Elementary School District 03 Buana Bakti Right Kerinci Regency Siak totaling 31 mother. Results of this study can be concluded Effect parenting to children's achievement level analysis shows that there is no influence of parenting on children's achievement levels. These results can be seen from the value of p = 0.970 (p> 0.05), with the value of the correlation coefficient of 0.003. The level of parental education and parental income levels have a greater contribution than the parenting parents in improving student achievement. Keywords: Parenting parents, academic achievement